2022
DOI: 10.1021/acsami.2c15869
|View full text |Cite
|
Sign up to set email alerts
|

Tetrazolyl Porphyrin-Based Hydrogen-Bonded Organic Frameworks: Active Sites-Mediated Host-Guest Synergy for Advanced Antimicrobial Applications

Abstract: Hydrogen-bonded organic frameworks (HOFs) with multiple functions and permanent pores have received widespread attention due to their potential applications in gas adsorption/separation, drug delivery, photocatalysis, proton conduction, and other fields. Herein, we constructed a three-dimensional (3D) HOF with 1D square channels by utilizing a dual-functional tetrazolyl porphyrin ligand bearing an active center of the porphyrin core and open sites of nitrogen atoms through π–π stacking and hydrogen-bonding int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Integrating porphyrins into HOFs can result in enhanced PDT efficiency and multifunctional carriers with versatile functional components. [16][17][18][19] Pyrene and analogues of its tecton by incorporating CH 3 -, F-, or NH 2 -groups on the ortho-position of the phenyl ring of the benzoic acids are another kind of active organic building block. A series of photoactive HOFs such as hydrogen-bonded biohybrid frameworks (HBFs 1-3), 20 hydrogen-bonded framework-101 (HOF-101) [21][22][23][24] and porous materials from FJIRSM, CAS (PFC-1) 11 are synthesized with highly extended p-conjugation structures.…”
Section: Formulation Of Hof-based Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating porphyrins into HOFs can result in enhanced PDT efficiency and multifunctional carriers with versatile functional components. [16][17][18][19] Pyrene and analogues of its tecton by incorporating CH 3 -, F-, or NH 2 -groups on the ortho-position of the phenyl ring of the benzoic acids are another kind of active organic building block. A series of photoactive HOFs such as hydrogen-bonded biohybrid frameworks (HBFs 1-3), 20 hydrogen-bonded framework-101 (HOF-101) [21][22][23][24] and porous materials from FJIRSM, CAS (PFC-1) 11 are synthesized with highly extended p-conjugation structures.…”
Section: Formulation Of Hof-based Biomaterialsmentioning
confidence: 99%
“…Zhu's group constructed a HOF (named JZS-1) with persistent open channels using tetrazolyl porphyrin as the building blocks and ulteriorly fabricated nanomaterials of JZS-1 with a simple physical top-down method for more superior performances. 19 On account of the confined space and abundant interactive sites exposed on the inner wall of the pores, JZS-1 can achieve size- and charge-selective adsorption toward cationic dyes. The authors found that the binary material executed the best performances in PDT at a certain concentration of MB (methylene blue) (MB@JZS-1 0.33% ) due to the distribution of MB and the resulting changes in structure and electronic cloud of the whole material.…”
Section: Biomedical Applications Of Hofsmentioning
confidence: 99%
“…Besides, porphyrin monomers have also been constructed into hydrogen-bonded organic frameworks (HOFs), which could produce a large amount of 1 O 2 , and have a significant inactivation effect on S. aureus under the irradiation of red light. 132 Compared with inorganic semiconductors, the exciton binding energy of pure COFs is relatively high. 133 To overcome this inherent shortcoming, Zhang and colleagues successfully synthesized a COF@CD composite by linking the COF and CDs via hydrogen bonds.…”
Section: Catalysis Science and Technology Reviewmentioning
confidence: 99%
“…[3] Over the past decade, a series of functional organic groups such as À DAT, [1a,4] À COOH, [1d,5] À CHO, [6] À CN [7] have been developed for the construction of HOFs. Accordingly, many HOFs materials have been realized for diverse applications including gas separation, [8] gas storage, [9] heterogeneous catalysis, [10] sensing, [11] drug delivery [12] and biomedical applications. [13] HOFs can be easily regenerated through simple recrystallization, making them as very promising porous materials for their practical applications.…”
Section: Introductionmentioning
confidence: 99%